PELAYANAN PUBLIK DI PUSKESMAS RAWAT JALAN SIAK HULU I KECAMATAN SIAK HULU KABUPATEN KAMPAR TAHUN 2017 - Purba, Elisabet Duma Novita; ", Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
One of the implementation of public services, namely at the Siak Hulu I Health Center, Siak Hulu District, Kampar Regency, was found phenomena such as the lack of awareness of medical staff on the time of service to patients, the absence of pulmonary TB specialists and damaged and unavailable facilities and infrastructure. Then the formulation of the problem made by the researchers are: (1) How is public service at the Siak Hulu I Outpatient Health Center in Siak Hulu District, Kampar Regency in 2017? , (2) What are the factors inhibiting public services in the Siak Hulu I Outpatient Health Center in Siak Hulu District, Kampar Regency in 2017?. This study aims (1) to describe public services at the Siak Hulu Outpatient Health Center in Siak Hulu District, Kampar Regency in 2017, (2) to explain the inhibiting factors of service at the Siak Hulu I Outpatient Health Center in Kampar District in 2017. This study using a qualitative approach to the type of descriptive research. Data collection techniques are done by interview and documentation study. While the data analysis techniques used are descriptive qualitative data analysis techniques. The results of the study found that of the seven Service Standards in the Ministry of Administrative Reform and Bureaucratic Reform No. 36 of 2012 it was still found that the services at the 2017 Siak Hulu I Public Health Center were not well implemented. So the advice given is to increase the operational hours of the puskesmas by submitting it to the department, posting information with the latest technology, tightening the rules, and completing facilities and infrastructure.Â Keywords: Affordable services, Fast and cheap services, Service Mechanisms and Procedure